Imagining Consumers Design and Innovation from Wedgwood to Corning - Blaszczyk, Regina Lee.; Project Muse.; Project Muse. (2019)
In contrast, companies that tried to stimulate desire, reshape taste, and encourage profligate spending by using the tools of persuasion - mass advertising, extravagant styling, and installment selling - found their efforts thwarted, for consumers refused to buy products that they did not really want."--Jacket.
"Imagining Consumers is the first book to tell the story of American consumer society from the perspective of mass-market manufacturers and retailers. It relates the trials and tribulations of china and glassware producers in their contest for the hearts of working- and middle-class women, who by the 1920s made up more than 80 percent of those buying mass-manufactured goods. Following a model pioneered by Josiah Wedgwood during Great Britain's eighteenth-century industrial revolution, successful American manufacturers closely collaborated with retailers to sort out consumer priorities and tailored their products accordingly.
Cinderella Stories -- China Mania -- Beauty for a Dime -- Fiesta! -- Better Products for Better Homes -- Pyrex Pioneers -- Easier Living? -- Essay on Sources.
Open access edition supported by the National Endowment for the Humanities / Andrew W. Mellon Foundation Humanities Open Book Program.
The text of this book is licensed under a Creative Commons Attribution-NonCommercial-No Derivatives 4.0 International License
Originally published as Johns Hopkins Press in 2000
Includes bibliographical references and index.
Description based on print version record.
Keywords: Consumers' preferences -- Great Britain -- History; Consumers' preferences -- United States -- History; Glassware industry -- Great Britain -- History; Glassware industry -- United States -- History; Ceramic tableware industry -- Great Britain -- History; Ceramic tableware industry -- United States -- History; USA; Electronic books; History; Electronic books